2014
DOI: 10.1128/genomea.00911-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Whole-Genome Sequence of Serratia marcescens Strain MCB, Associated with Oscheius sp. MCB (Nematoda: Rhabditidae) Isolated from South Africa

Abstract: Here we report on the draft genome sequence of Serratia marcescens strain MCB associated with Oscheius sp. MCB (Nematoda: Rhabditidae) isolated from South African soil. S. marcescens strain MCB has 5,304,212-bp genome size with 4,877 genes and a G+C content of 59.1%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…The genome of Serratia sp. strain TEL was found to be 5,000,541 bp in size, with a G+C content of 59.1%, which was similar to that of other Serratia species ( 11 13 ). Furthermore, the contigs were annotated using the NCBI Prokaryotic Genome Automatic Annotation Pipeline.…”
Section: Genome Announcementsupporting
confidence: 58%
“…The genome of Serratia sp. strain TEL was found to be 5,000,541 bp in size, with a G+C content of 59.1%, which was similar to that of other Serratia species ( 11 13 ). Furthermore, the contigs were annotated using the NCBI Prokaryotic Genome Automatic Annotation Pipeline.…”
Section: Genome Announcementsupporting
confidence: 58%
“…The smaller the e-value, the higher the chance of matches not to be random, but due to relativeness. The accession MCB was already supported as entomopathogenic (Serepa and Gray, 2014). The isolate Oscheius sp.…”
Section: Discussionmentioning
confidence: 92%
“…The calculated ANI between ano1 and ano2 shows 100% identity, indicating that S. marcescens ano1 and ano2 were the same strain (Figure 1 ). ANI values indicated that these two isolates belong to S. marcescens species as they were more than 95% identical to those in S. marcescens MCB (Serepa and Gray, 2014 ) and S. marcescens Db1 (Flyg et al, 1980 ), previously isolated from nematodes and fruit flies, respectively (Figure 1 ). Serratia sp.…”
Section: Resultsmentioning
confidence: 69%